(untitled) (Damascus University Journal of agriculture sciences, 2025)
Abstract Apple pomace consider one of the organic waste in Syria, which can be a source of clean energy if treated anaerobically. this research aim to investigate the effect of adding apple pomace to caw manure on producing biogas. The batch experiences were conducted in laboratory-scale digesters on substrates added apple pomace with rates 12.5%, 25% and 37.5%, at a laboratory temperature, for 42 days, and compared it with substrates untreated by adding apple pomace. The results showed that treatment of cow manure substrates by adding apple pomace with rates 12.5%, 25% and 37.5%, significantly increased the production of Biogas compared with untreated substrates which produced 11.76 LN kg-1 OTS biogas. The results also showed that treatment by adding apple pomace with rates 25% to the substrates is the best tested treatments methods which produced 65.99 LN kg-1 OTS of biogas compared to untreated substrates.